Diseño y construcción de una incubadora para el período neonatal en canes para el control de variables de temperatura, humedad y oxigenación del aire. - Chiguano Allauca, José Israel (2022)
The actual project describes an incubator implementation with an environment, what allows the air temperature, humidity and oxygenation variables control, inside the cabin, through a PID control, during the neonatal dog period. At present, the main problem, what presents incubators is having an on-off control, which the systems fluctuate and it was implemented a PID control, for the temperature and air oxygenation and an on-off control for relative humidity, at being a slow process of humidification. It was used the interview and survey technique, which support the environmental risks factors material and range with veterinarians and related scientific research to a dog care, during its neonatal period. The project arises from the need an incubator, which allows the environmental risk factors measurement and monitoring, what are exposed as: thermoregulation, renal function, air oxygenation with several located sensors inside the cabin, the control is made, through the use dth21, dth11, mq-9 sensors and control modules: dimmer, relay, H bridge, which allow temperature reading and control by varying the two infrared lamps, humidity electrical flow with on and off an ultrasonic humidifier, the passenger compartment inside air oxygenation with a forced ventilation system, by two fans with a clockwise and counterclockwise direction. Acquisition, processing, and serial communication between the (TAD) data acquisition card and Raspberry Pi 4 B+, what allows the value entry by controlling for air temperature, humidity and oxygenation, through the temperature results display, air humidity and oxygenation, by graphs that represent the variable signal value to measure on a Wave share capacitive screen. It was got the air temperature, humidity and oxygenation curve, through the Arduino Mega serial monitor, by applying a step-type input with a 22.2 min, 23.33 min and 13.33 min, time, respectively for the PID system to control each of the variables. It was developed a graphical interface in the Thonny Python environment about Raspberry and each of monitoring and control buttons for entering the temperature, humidity and air oxygenation set point.